Fluid structural interface of force excitation on pipeline elbow joint - Aman, Ahamad (2013)
Piping systems are one of the most reliable and safest means of transfer of matter and energy. The length of the piping system can archieve hundreds of kilometers and belong the piping system can occur mechanism failure modes including cracking, lage deformation, buckling, fracture, local damage, corrosion and clogging of piping systems. Piping system has a lot of connector along its connection. For example equal elbow, T-Joint , Pipe nipple and Pipe Offset. The connectors has their own problem and that problems can cause accident. So,it is important for engineer to design the systems safely in order to prevent accident. So, it is a responsibility for engineers to make researches in other to improve the piping system